The advisory opinion on obligations of states in relation to climate change: the beginning of a new phase towards climate justice? - Pinto-Bazurco Barandiarán, Jose Félix (2023)
The General Assembly of the United Nations recently sent a request to the International Court of Justice to prepare an advisory opinion to clarify two Relevant Issues on State Responsibility in International Law regarding climate change: (a) What are the obligations of the States to guarantee the protection of the climate and environment of anthropogenic greenhouse gas emissions greenhouse? and (b) What are the legal consequences for States, when, for their actions and omissions, have caused significant damage to the climate system and environment environment, particularly to the most vulnerable States and to the peoples and individuals of present and future generations? This article analyzes the content of the request and the possible effects of the advisory opinion.